Hubungan Self-Regulated Learning Dalam Pembelajaran IPS dengan Adiksi Media Sosial Tiktok pada Peserta Didik di SMP Pasundan 12 Bandung: The Relationship Between Self-Regulated Learning in Social Studies Education with TikTok Social Media Addiction Among Students at SMP Pasundan 12 Bandung - Risma Yanti, Ressa; Supriadi, Acep; Rakhman, Muhammad Arief (Moderasi: Jurnal Studi Ilmu Pengetahuan Sosial, 2025)
One of the most popular social media platforms among students is TikTok, a short-video sharing platform widely used for entertainment. However, excessive and uncontrolled use of TikTok can negatively impact learning activities, such as decreasing the ability to manage time, plan tasks, and complete academic responsibilities independently. These abilities are referred to as Self-Regulated Learning (SRL). In social studies (IPS) learning, SRL plays a crucial role as it helps students understand concepts, manage their study time, and complete tasks in a structured manner. With strong SRL skills, students can maintain focus in IPS learning despite distractions like social media. This study aims to analyze the relationship between SRL in IPS learning and addiction to the social media platform TikTok. The research employs a quantitative approach using a correlational method and purposive sampling technique involving 196 respondents. The data analysis results show a significance value of 0.000 < 0.05 and a Pearson correlation coefficient of -0.440, indicating a significant negative relationship between SRL in IPS learning and TikTok addiction. This means that the higher the level of students' self-regulation in IPS learning, the lower their tendency to experience TikTok addiction. These findings highlight the importance of strengthening self-directed learning strategies to reduce the negative impacts of social media use. Keywords: Self-Regulated Learning, Social Studies Learning, TikTok Social Media Addiction.